Evolution of the cluster development concept: from agglomeration theory to ecosystems - L. A. Gamidullaeva; E. P. Strakhov (Модернизация, инновация, развитие, 2023)
Purpose: of the study is to substantiate the relationship between cluster theory and ecosystem concepts on the basis of systematization of scientific research directions on the problem of economic clustering.Methods: the study is based on the theories of regional, spatial economics, innovative development, network and ecosystem economics, presented in the works of the Russian and foreign scientists. To solve the tasks set, general scientific methods (analysis, synthesis, description, comparison, induction, historical, classification, etc.) and special methods (bibliometric and content analysis of literature, statistical) were used. In order to conduct bibliometric analysis, a standardized methodology for exploratory analytics was applied using the tools provided in modern computer data analysis packages.Results: on the basis of thematic selections from the Scopus database, the systematization of the most cited scientific publications on the problem of cluster development, published for the period 1997-2022 was carried out. A qualitative content analysis of the content of text arrays, followed by a meaningful interpretation of the identified patterns, made it possible to group the main directions of scientific thought in this area and identify promising areas for the further research. A conceptual scheme for the evolution of the formation and development of the cluster concept: the key theories and approaches that determined the trajectory of its development are identified.Conclusions and Relevance: the hypothesis that the ecosystem concept is an evolutionary development of cluster theory is confirmed. It is concluded that in the future the topic of innovative ecosystems is highly likely to move into the category of the basic ones devoted to cluster development. Despite the similarity (in the first approximation) of clusters and ecosystems, these approaches differ fundamentally in many criteria, primarily in terms of the proposed mechanisms for building interaction between participants, organization and regulation. In order to use the ecosystem approach in the practice of regional and industrial policy, its further conceptual, methodological and instrumental support is necessary.